Climate change resilient health facilities: a scoping review of case studies in low and middle-income countries - Schwerdtle, Patricia; Ngo Tuan Anh; Hasch, Fabia; Phan, Thao Vy; Quitmann, Claudia; Montenegro Quiñonez, Carlos Alberto (Environmental research letters, 2024)
Resilient health systems can reduce the negative health and social effects of climate change. However, health systems are themselves threatened by climate change through climate hazards increasing the demand for services, threatening health infrastructure and supply chains, and stressing the workforce. While there is significant research on the environmental sustainability of health facilities in high-income countries, less attention has been paid to building climate resilience (sustainably), especially in low- and middle-income countries (LMICs). This scoping review aims to connect top-down guidelines with concrete bottom-up activities to accelerate transformational change in the health sector. We systematically and comprehensively searched the academic and grey literature to identify case studies of climate-resilient health facilities in LMICs and describe the activities that build resilience to climate-related health risks. We used scoping review methodology (Arksey and O’Malley 2005 Int. J. Soc. Res. Methodol. 8 19-32; Levac et al 2010 Implement. Sci. 5 69) and employed a two-phase, double-blinded, screening approach to search the academic and grey literature (from 2015 to 2022). We searched four academic databases (Scopus, PubMed, CINAHL, Lilacs), Google Scholar and key websites from the World Health Organisation (WHO), Green Climate Fund, Global Adaptation Mapping Initiative, Health Care Without Harm, and the Global Environmental Facility. A coding framework guided data extraction and data were analysed quantitatively and qualitatively. We identified 26 case studies in 46 countries outlining planned and implemented activities to develop the climate resilience of health facilities in LMICs. We focussed on activities targeting health care facilities rather than broader health systems level planning and present a narrative synthesis of these activities using the WHO Operational Framework for Climate-Resilient and Low Carbon Health Systems. As a result, we developed a conceptual theory of change model that can be applied to various health settings to guide vulnerability assessments and improvement plans to build climate resilience. The research sought to identify successful efforts to build climate resilience at the facility level in LMICs, yet we found very little evidence of actual implementation and no evaluations. Of the case studies that were identified, the activities mapped neatly onto the WHO Operational Framework with some novelties and nuances. Key enablers to building climate resilience include supportive policies, strong information systems, stakeholder coordination, adequate funding, and technical expertise. Community engagement emerges as an important consideration and is recommended for inclusion in climate resilience frameworks, action plans, and strategies. Bridging the knowledge-action gap can be helped by collating experiences, standardized reporting of initiatives, and increased investment in implementation science. Lessons learned and good practices should be shared among health decision-makers within and between countries, allowing for mutual learning. There is also an urgent need to ensure climate finance reaches the health facilities and populations most at risk.